Relatório de Estágio Profissional - "Confronto com duas realidades da Profissão Docente: Retrospetiva da Caminhada de um Estudante Estagiário no contexto escolar" - Álvaro Luís Pisco de Moura (2017)
The teacher profession is complex and unpredictable, requiring an initial training that prepares future teachers for this context, specifically in the acquirenment of ability to transform academic knowledge into professional knowledge by the pre-service teacher. This document reports the practicum training of a pre-service teacher who entered with very high expectations, but who in the confrontation with reality, realized the difficulty of the teacher's mission. In this context, the making of the report addresses the reconstruction of the most relevant moments of the pre-service teacher journey (the author), and is structured in the process of building his professional identity. In terms of structure, the document is organized into five major chapters. The first chapter includes the sports and academic path, as well as the expectations for the practicum training year. In the second it is overt the cooperating school characterization as well as the importance of the practicum training. The third chapter concerns the way that the teaching-learning process is organized and managed, in direct confrontation with the school reality. In the fourth chapter is presented a curricular test in volleyball using the model Teaching Games for Understanding. In the fifth chapter, the extracurricular activities performed by the pre-service teacher during the practicum. The sixth and final chapter builds around small excerpts from students, faculty and staff 's' speeches', which depict the memories the trainee left behind in those he dealt with during the practicum training year. The document concludes with the main conclusions about the teaching conception of the pre-service teacher, as a result of the experience in the school context.